A world beyond hydrogen bonds?: Chalcogen-chalcogen interactions yielding tubular structures - Gleiter, Rolf; Werz, Daniel B.; Rausch, Bernhard J. (Chemistry - a European journal, 2003)
It is shown that tubular structures arise in the solid state through close chalcogen-chalcogen (X⋅⋅⋅X) contacts. As examples a variety of cyclic systems containing sulfur and selenium centers is presented. Common to all of them are close contacts between the chalcogen centers of neighboring stacks giving rise to a zigzag or ladder-type arrangement. In the case of cyclic systems of ring size 24-33 the resulting tubes are able to include hydrocarbons as guest molecules. For 2,7-ditelluraocta-3,5-diyne (17) the close contacts between the tellurium centers of the acyclic C2 symmetric building blocks generate a helical arrangement in which n-hexane was included. The favored X⋅⋅⋅X contacts can be traced back to np(X)-σ*(XC) interactions.